Respon Pertumbuhan dan Hasil Tanaman Terung terhadap Pemberian Dosis Pupuk Kandang Kotoran Itik pada Lahan Rawa Lebak - Fahriadi Fahriadi; Mahdiannoor (Rawa Sains: Jurnal Sains STIPER Amuntai, 2011)
Eggplant plants can grow on all types of land used for agricultural cultivation, but are not good if planted in lowland because of poor supply of nutrients so that special treatment is needed to improve it by giving duck manure so that the growth and yield of eggplant plants can be optimal. Giving organic fertilizer can improve physical, chemical and biological properties of lowland soil. This study aims to (i) determine the growth response and yield of eggplant plants on dosing duck manure dosages application on lebak lowland, (ii) determine the best dosage of duck manure on the growth and yield of eggplant on lebak lowland. This research was conducted in Rantawan Village, Amuntai Tengah District, Hulu Sungai Utara Regency, from May - August 2010, using a Randomized Block Design (RBD), with 5 treatments and 4 replications, so that there were 20 experimental unit. The treatments tested were 5 doses of duck manure, t0 = 0 t ha-1, t1 = 10 t ha-1, t2 = 20 t ha-1, t3 = 30 t ha-1, t4 = 40 t ha-1. The results showed no response to plant height aged 14 and 21 days after planting (DAP), the real response of the number of leaves aged 14 DAP, and the response was very significant the number of leaves aged 14, 21 and 35 DAP due to the application of duck manure dung fertilizer. The best dosage of duck manure for growth and eggplant yield on lebak lowland is t1, which is 10 t ha-1